The Problem of Context in Comparative Education Research - Noah W. Sobe; Jamie Kowalczyk (LED Edizioni Universitarie, 2013)
This paper argues that comparative education researchers - and education researchers generally - should pay more attention to how they conceptualize the Context(s) of schools and education systems. The construction of «the research context» is caught up in the mobilization of norms, power relations, regulative principles, technologies and strategies. Ascriptions of Context can operate as externally imposed categories that enclose, disable, and deny access to resources, opportunities, agency, and subject positions. In like measure, inscriptions of Context can sometimes enable, increase access and generally privilege particular cultural groups or particular social settings. This paper offers methodological strategies for analytically approaching the problem of Context in educational research. We propose that challenge is to understand how Context is part of an interweaving process with an object/objects within an assemblage that is ever changing. The «entangled analysis» approach (Sobe, forthcoming) advanced here attends to the constructed and constructing quality of Context. And it necessarily brings the researcher into the problematic, as she too is continually within the power/knowledge relations that make Contexts meaningful and consequential. We are argue that «contextualizing» a study should not be merely a preparatory activity but should carry across the entirety of a research project. Rather than beginning with standardized Contextual categories researchers should seek to understand the confluence of practices and objects that are coming together as well as constantly flowing and changing.